Konseling Musik untuk Mereduksi Kecemasan Berbicara di Depan Kelas Pada Siswa SMPN 19 Jambi - Amaliah Alfadhilah; Nelyahardi Nelyahardi; Muhammad Ferdiansyah (Jurnal Bimbingan dan Konseling Ar-Rahman, 2023)
Anxiety about speaking in front of the class can be said to be an obstacle in the student learning process. One way to reduce it is to use music therapy. The purpose of this study was to reveal the effectiveness of using music therapy to reduce students' anxiety about speaking in front of the class. This research uses Quasi Experimental Design or quasi-experimental research using Pretest Posttest Nonequivalent Control Group Design. The population in this study were students in class VIII A & VIII B totaling 59 people. The sample in this study was 30 students who were taken by purposive sampling technique. The results of this study indicate that the anxiety of students speaking in front of the class in the experimental class for the pretest is 1546 and for the posttest is 1245. As for the control class, that is for the pretest it is 1454 and for the posttest it is 1340. Based on the results of the t-test calculation, Tcount is obtained which is equal to -2.553. The value of Ttable with Sig. (2-tailed) 0.05, which is 2.160. The hypothesis is accepted or music therapy is effective in reducing students' anxiety about speaking in front of class VIII A SMP Negeri 19 Jambi City. _____________________________________________________________ Kecemasan berbicara di depan kelas dapat dikatakan sebagai penghambat dalam proses belajar siswa. Salah satu cara untuk menguranginya ialah menggunakan terapi musik. Tujuan penelitian ini mengungkapkan efektivitas penggunaan terapi musik untuk mereduksi kecemasan siswa berbicara di depan kelas. Penelitian ini menggunakan jenis Quasi Experimental Design atau penelitian eksperimen semu dengan menggunakan Pretest Posttest Nonequivalent Control Group Design. Populasi pada penelitian ini ialah siswa kelas VIII A & VIII B berjumlah 59 orang. Sampel pada penelitian ini berjumlah 30 orang siswa yang diambil dengan teknik purposive sampling. Hasil penelitian ini menunjukkan bahwa kecamasan siswa berbicara di depan kelas pada kelas eksperimen untuk pretest yakni sebesar 1546 dan untuk posttest sebesar 1245. Sedangkan untuk kelas kontrol yakni untuk pretest sebesar 1454 dan untuk posttest 1340. Berdasarkan hasil perhitungan t-test di peroleh Thitung yaitu sebesar -2,553. Adapun nilai dari Ttabel dengan nilai Sig. (2-tailed) 0,05 yaitu sebesar 2,160. Hipotesis dinyatakan diterima atau terapi musik efektif untuk mereduksi kecemasan siswa berbicara di depan kelas VIII A SMP Negeri 19 Kota Jambi.